Intergenerational mobility in self-employment: a regional approach - Hannu Niittykangas; Hannu Tervo (European Regional Science Association (ERSA), 2002)
Self-employment is an important option in the work careers of many. It may be seen as a learning process illustrated for example in the social development model by Gibb and Ritchie (1982) and in the model of entrepreneurial careers by Dyer (1994). In the former, entrepreneurship is mainly seen in terms of the situations which individuals encounter and the social groups to which they relate. Among many others, family background, education and work experience have an effect directly, or indirectly through intentions (see Krueger and Carsrud 1993)on becoming self-employed. The children of parents owned a business are more likely to see such a career as more acceptable than working for someone else. An individual who has a self-employed parent possess a kind of 'entrepreneurial human capital'. Family background may provide self-confidence and social support, a supply of resources needed by the business, and strategic capacity to learn and organise for new activities. The movement to self-employment may also simply arise because children tend to inherit family firms. This paper analyses self-employment among children with parents owned a business based on the Finnish Longitudinal Census data and the Longitudinal Employment statistics from the period of 1970 to 1995 (1998). This exceptionally wide register based data makes possible the examination of intergenerational mobility in different regions. In the data file, individuals belonging to age-group 0-14 years as of 1970 have the socio-economic status, industry and occupational status of their household reference person, mostly the father, included in their record. Our sample is consisted of those children in 1970 who are from families of self-employed. The aim of this paper is to describe and model the swift into self-employment among children of self-employed parents. The explanatory variables are divided into three categories: family background, individual characteristics, and regional features. The analysis refers to the year 1995, and when possible, to the year 1998. Follow-up of individuals throughout the study period will also be made. Main questions concern the role of family background, sex, education, industry and region in the inheritance of entrepreneurship. The results are also compared with the results based on a sample of individuals belonging to the same age group but with non self-employed parents.
Keywords: 330